Foot and mouth disease vaccine efficacy in Africa: a systematic review and meta-analysis - Wubshet, Ashenafi Kiros; Werid, Gebremeskel Mamu; Teklue, Teshale; Zhou, Luoyi; Bayasgalan, Chimedtseren; Tserendorj, Ariunaa; Liu, Jinjin; Heath, Livio; Sun, Yuefeng; Ding, Yaozhong; Wang, Wenxiu; Zaberezhny, Alexei D.; et al. (Frontiers in Veterinary Science, 2024)
Background Several factors, such as diverse serotypes, vaccination methods, weak biosecurity, and animal movements, contribute to recurrent Foot-and-Mouth Disease Virus (FMDV) outbreaks in Africa, establishing endemicity. These outbreaks cost over $2 billion annually, prompting a high-priority focus on FMDV vaccination. Despite extensive efforts, vaccine efficacy varies. This study aims to evaluate routine foot and mouth disease (FMD) vaccines in Africa via systematic review and meta-analysis. Methods A systematic review and meta-analysis were carried out following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Meta-analysis was conducted to assess the efficacy of FMDV vaccination using the meta for package of R. Results Vaccinated animals have roughly a 69.3% lower chance of FMDV infection compared to unvaccinated animals, as indicated by the pooled results from the random-effects model, which showed a risk ratio (RR) of 0.3073. There was a statistically significant heterogeneity (p < 0.05) across all of the included articles. Conclusion Overall findings suggest that if properly planned and implemented, FMDV vaccination programs and strategies in Africa could help control the spread of the disease throughout the continent and beyond.